2019
DOI: 10.5114/wiitm.2019.88647
|View full text |Cite
|
Sign up to set email alerts
|

Reconsideration of indications for choledochoscopic gallbladder-preserving surgery and preventive measures for postoperative recurrence of gallstones.

Abstract: Introduction: The recurrence of cholecystolithiasis after choledochoscopic gallbladder-preserving surgery is a major problem. It is unclear whether the recurrence of cholecystolithiasis is due to the limitations of the operation itself or to the selection of inappropriate candidates. Aim: To analyze the recurrence of cholecystolithiasis after choledochoscopic gallbladder-preserving surgery and to provide guidance for the treatment of cholecystolithiasis by choledochoscopic gallbladder-preserving surgery. Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Despite these advantages, the recurrence of gallstones is a significant problem related to minimally invasive GPS, causing patients a lot of worry. To solve this problem, many researchers have sought preventive measures for stone recurrence ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these advantages, the recurrence of gallstones is a significant problem related to minimally invasive GPS, causing patients a lot of worry. To solve this problem, many researchers have sought preventive measures for stone recurrence ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most of our patients had a BMI more than 25 kg/m 2 . For these patients, preoperative and postoperative management of weight should be carried out to prevent stone recurrence, which is also the direction of our further efforts in management of patients in the future [13].…”
Section: Discussionmentioning
confidence: 99%
“…With surgeons' accumulated experience in this area and the development of a proposed clinical guideline in recent decades, laparoscopy combined with choledochoscopic lithotomy has been gradually proven to be safe and effective with a relatively low rate of gallstone recurrence ( 15 , 16 ). A recent retrospective study ( 17 ) showed that the overall recurrence rate of cholecystolithiasis was 9.66% among 145 patients after choledochoscopic gallbladder-preserving surgery with a median follow-up of 36 months, and the estimated 5-year recurrence rate for all patients was 12.5%. Our research group found that most cases of gallstone recurrence occurred within 2 years postoperatively, in line with a previous report ( 18 ).…”
Section: Introductionmentioning
confidence: 99%